Dealing With Welfare Conditionality 2019
DOI: 10.1332/policypress/9781447341826.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Resisting welfare conditionality: constraint, choice and dissent among homeless migrants

Abstract: This chapter examines the ways in which welfare conditionality impacts upon homeless migrants in the UK. Legal status, eligibility requirements and behavioural controls determine access to benefits, housing and State assistance, compounding the precarity of homeless migrants who are situated at the interstices of multiple (and competing) systems. The chapter looks how specific conditions both constrain the choices of homeless migrants and how efforts at behavioural change are resisted. Using data from a study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Such deficit-based, 'pathological' models of disadvantage overlook the capacity of individuals to exercise personal choice, preference and values in even the most constrained of circumstances. Elsewhere, I have pointed to a certain blindness to agency in conversations about homelessness (Serpa 2019). In a similar vein, Aldeia's (2013) governmentality analysis of homelessness research revealed a 'dominant regime of truth', constituted by two separate (but complementary) approaches to investigating the phenomenon: quantification and 'pathological individualization' (p. 64) 8 .…”
Section: Discussion: Authentic Voice In Critical Poetic Inquirymentioning
confidence: 98%
“…Such deficit-based, 'pathological' models of disadvantage overlook the capacity of individuals to exercise personal choice, preference and values in even the most constrained of circumstances. Elsewhere, I have pointed to a certain blindness to agency in conversations about homelessness (Serpa 2019). In a similar vein, Aldeia's (2013) governmentality analysis of homelessness research revealed a 'dominant regime of truth', constituted by two separate (but complementary) approaches to investigating the phenomenon: quantification and 'pathological individualization' (p. 64) 8 .…”
Section: Discussion: Authentic Voice In Critical Poetic Inquirymentioning
confidence: 98%